Citizenship, Migration and Free Movement in Brexit Britain. (1st July 2016) - Shaw, Jo
Abstract : Regardless of what happens in the next few months and years in the post-referendum UK, much of the harm has been done. The uncertainty, in particular, is killing. It will have a significant impact on many of the UK's most productive economic sectors including universities and financial services. It will cast a shadow over inward investment and over the willingness to take risks of those responsible, for example, for building new infrastructure. There will be a brain drain. Already in some respects the EU is acting as if the UK were no longer a Member State. It has no Commissioner since Jonathan Hill's resignation. After the EUCO summit on 29 June which took pace without the UK's presence, EU27 conclusions were issued.